Unbalanced species losses and gains lead to non‐linear trajectories as grasslands become forests. (30th October 2019) - Kimberley, Adam; Bullock, James M.; Cousins, Sara A. O.
Abstract: Questions: Rates of plant community shifts after environmental changes depend on how quickly affected species are gained and lost. Understanding how the balance between extinction and colonisation varies over time, and how it is influenced by local and landscape factors, is essential to understanding overall change trajectories. Investigating change requires data at several time steps over sufficient periods, and the paucity of such data represents an important knowledge gap. We ask: (a) how variation over time in the rates of species' extinction and species' colonization controls the trajectory of biodiversity change in abandoned semi‐natural grasslands? and (b) can landscape composition and habitat history modify change trajectories by acting independently on groups within plant communities? Location: Sweden, Stockholm Archipelago. Methods: We use data on plant composition, management history and landscape context in former grasslands, abandoned at different points since 1901, in a space‐for‐time analysis, comparing rates of grassland species loss and forest species establishment and investigating resulting biodiversity trajectories. Results: Grassland species declined steeply in recently abandoned habitats before levelling off, while the accumulation of forest species was linear, with no plateau reached even at the longest time since abandonment. Hence, we observed a trough in biodiversity, with an initial decline in overall species richness followed by a partial recovery. Only forest species gain was enhanced by nearby habitat availability. Conclusions: Information on community compositional changes over short time periods may be misleading about the extent and even direction of ongoing biodiversity gains and losses. Moreover, the non‐linear changes observed suggest thresholds in time, after which succession to the forest community accelerates and the ability to manage a return to the grassland community diminishes. Accounting for the combined influence of landscape composition and history is key to fully understanding community shifts over time. Abstract : Extinction and colonisation rates following environmental change determine trajectories of plant community change. We show that in abandoned grasslands, variation in the balance between extinction and colonisation can lead to non‐linear changes in overall biodiversity over time. Compositional changes over short time periods may therefore be misleading about the extent and even direction of ongoing biodiversity gains and losses.